Fundamental of Entrepreneurship ENT 300: The Dashing Diva / Nurul Hazwani Saimi... [et al.] - Saimi, Nurul Hazwani; Taka, Loretta; Gambal, Prisca; Herman, Beatrice Nasip; Aban, Siti Aishah (2015)
Dashing Diva is in the form of partnership and wholly own by five Bumiputera entrepreneurs. We provide our customer with high quality services based on knowledge in managing business, dealing with customers, satisfying the customers and meeting all demands. Our motive on why we chose this business is ladies love their nails or even mens out there. They make our hands look elegant and feminine and we would like them to be strong and pretty. However, a lot of people out there have problems with their nails.